Analysis of Residential Well Water Quality Around People's Gold Mines in the Tourist Area of Dusun Selindungan - Rachmawati Noviana Rahayu; Suripto; Hilman Ahyadi (Jurnal Penelitian Pendidikan IPA, 2024)
The Sekotong area has natural charm and potential mining. This area is one of the preferred destinations for visits by local and foreign tourists. However, apart from that, the Sekotong area is also famous as a community gold mining area. Mining activities carried out still use traditional methods, which are very far from environmentally friendly principles, so they can have impacts, including causing a decrease in the quality of residential well water. This research was conducted to determine the water quality of residential wells around community gold mining in the tourist area of Dusun Selindungan Eleven well water samples were taken using a purposive sampling method based on the distance of the well to the source of gold mining waste disposal and are still used by residents to meet their daily needs. Physical, chemical and biological water quality parameters of water samples were investigated in the laboratory, except temperature and pH were measured directly in the field. Data for each water quality variable was analyzed to determine the pollution index. The results show that DO, TDS, content of phosphate, E. Coli bacteria and total coliforms in well water from the study area generally exceed quality standardsWell water in an area that is a different distance from the people's gold mining waste disposal site has each been contaminated with manganese and mercury, although it is still below quality standards.